Analisis Yuridis Tentang Kebiri Kimia Terhadap Pelaku Kekerasan Seksual Terhadap Anak (LEGAL DIALOGICA, 2025)
This study examines the Regulations on chemical castration punishment for perpetrators of sexual violence against children. This study uses the Juridical Legal Research or Normative Juridical research method. The researcher will apply the Library study system in this study. Literature review is a systematic process that involves searching, reviewing, and analyzing literature or written sources that are relevant to the research topic or problem being studied. Literature review involves collecting and analyzing various types of sources. The results of the study indicate that the Regulations on chemical castration punishment for perpetrators of sexual violence against children are regulated in Law No. 17 of 2016 Article 81 paragraph (7) and Article 81A paragraph (3), Chemical castration punishment is contrary to the protection of human rights according to positive law, this is in line with Article 28G paragraph (2) of the 1945 Constitution of the Republic of Indonesia and Article 33 of Law No. 39 of 1999. Writing recommendations: (1) For law enforcers, in upholding justice for perpetrators of sexual violence against children, they should apply basic criminal sanctions to the perpetrators; (2) For the government, it would be best to review and revise existing regulations that are of a nature that ignores Human Rights.Abstrak:Penelitian ini mengkaji Pengaturan tentang hukuman kebiri kimia bagi pelaku tindak pidana kekerasan seksual pada anak. Penelitian ini menggunakan metode penelitian penelitian Yuridis Legal Research atau Yuridis Normatif. Peneliti akan menerapkan sistem studi Pustaka pada penelitian ini. Studi pustaka (literature review) adalah sebuah proses sistematis yang melibatkan pencarian, penelaaan, dan analisis literatur atau sumber-sumber tertulis yang relevan dengan topik penelitian atau masalah yang sedang dipelajari Studi pustaka melibatkan pengumpulan dan analisis berbagai jenis sumber. Hasil penelitian menunjukkan bahwa Pengaturan tentang hukuman kebiri kimia bagi pelaku tindak pidana kekerasan seksual pada anak diatur dalam UU No. 17 Tahun 2016 Pasal 81 ayat (7) dan Pasal 81A ayat (3), Hukuman kebiri kimia bertentangan dengan perlindungan hak asasi manusia menurut hukum positif hal ini sejalan dengan Pasal 28G ayat (2) UUD NRI 1945 dan Pasal 33 UU No. 39 Tahun 1999. Rekomendasi penulisan : (1) Bagi penegak hukum, dalam meneggakan keadilan kepada pelaku tindak pidana kekerasan seksual pada anak agar menerapkan sanksi pidana pokok kepada para pelaku; (2) Bagi pemerintah, sebaiknya meninjau kembali dan merevisi peraturan-peraturan yang telah berlaku yang sifatnya mengesampingkan Hak Asasi Manusia.